Hepatitis B among University Population: Prevalence, Associated Risk Factors, Knowledge Assessment, and Treatment Management - Syed Ayaz Kazmi; Abdul Rauf; Mohammed Merae Alshahrani; Ahmed Abdullah Al Awadh; Zahoor Iqbal; Raya Soltane; ElSayed Tag-Eldin; Altaf Ahmad; Zulqarnain Ansari; Zia-ur-Rehman (Viruses, 2022)
Background: Very few studies have been reported on hepatitis B in the State of Azad Jammu and Kashmir, Pakistan, and none of them are specific to the prevalence and causes of hepatitis B spread among educational institutes. This study aimed to estimate the prevalence of hepatitis B infection and its associated risk factors among the University of AJ and K population. Methods: An observational, cross-sectional, and analytical study was conducted with 7015 students and employees. Hepatitis B was detected by rapid immunochromatographic tests (ICTs), enzyme-linked immunosorbent assay (ELISA), and real-time quantitative PCR. A questionnaire and interview method was used to assess the disease knowledge and associated risk factors with hepatitis B through Chi-square, Fisher’s exact test, and paired t-test. Results: Of the participants, 150 (2.13%) were found positive for the hepatitis B surface antigen (57.3% male and 42.7% female). Only 0.3% participants were found fully vaccinated against the hepatitis B virus. Among ethnic groups, the Syed tribe was found more prevalent for hepatitis B infection (40.6%), while use of contaminated mourning blades (95% CI: p = 0.0001) was found as an overlooked risk factor. Hepatitis preventive awareness sessions were found to be very significant (p = 0.0001). Conclusions: The study showed that an overlooked risk factor is playing a key role in the spread of HBV in a tribe living worldwide, which must be addressed globally to eradicate hepatitis B. In Pakistan, a country-wide annual HBV vaccination program should be launched to control hepatitis B.